PROFESSIONAL EDUCATION OF VOCATIONAL SCHOOL STUDENTS - S. M. Markova; A. К. Narcosiev (Вестник Мининского университета, 2018)
Introduction: modern conditions of development of society cause the need for further development of the professional education connected with new requirements to the maintenance of the professional training corresponding to a certain level of development of culture, personal and professional qualities, scientific and technical development of productions reflecting character of the market relations.Professional education is aimed at the development of professional and personal qualities, skills to navigate at the labor market, to establish professional cooperation, which ensures successful employment.Thus, professional education is the Central link in the training of workers and specialists.The main purpose of this article is to determine the nature and characteristics of education in vocational schools, to identify effective methods of studying the problems of educational activity.Matherials and methods: in research theoretical and empirical methods of cognition are used: methods of the analysis of materials, the analysis of literature, the analysis of documents, the analysis of works, the analysis of orally transmitted ideas, methods of the analysis of the phenomenon of education in practice, oral polls (interviews, conversations), observations, written polls, experiment, and also complex, differentiated, integrationally-methodical, polytheistic approaches.Result of the research: professional education is expressed in the unity of socialization and professionalization of the individual. A professionally developed personality is considered as a socially-professionally - integrative type of its orientation and efficiency.Professional education is considered as a set of three components: personality orientation, technical processes management, management  of technological methods of activity, which determines the effectiveness of professional work. The main integrator of professional education of future workers and specialists are objective and subjective factors of personal development, mutually supporting the success of the solution of personal, professional and social-life tasks.Universal values are of fundamental importance for professional education from the point of view of humanistic orientation, socio-economic transformations.The system of educational values highlights civil, cultural, socio-pedagogical, professional and environmental values. The formation of these values requires the implementation of integrative and professional sociological approaches to the education of workers and specialists.For professional activities, it is considered appropriate to create common and particular professional values, reflecting the specific occupations and activities.Discussion and Conclusions: the essence of professional education is defined, features of methods of research of problems of professional education, the factors influencing spiritually-moral and professional development of future workers and experts are revealed.